Konstruksi Frasa Dalam Novel Santri Pilihan Bunda Karya Salsyabila Falensia - Wulandari, Yetri; Lisdayanti, Septina; Yuniati, Ira; Kusmiarti, Reni (Journal Of Dehasen Educational Review, 2025)
The problem in this study is the construction of phrases in the novel Santri Pilihan Bunda by Salsyabila Falensia. The purpose of this research, namely: to analyze what types of phrases are most widely used in the novel Santri Pilihan Bunda Karya Salsyabila Falensia and describe the phrase construction in the novel Santri Pilihan Bunda Karya Salsyabila Falensia. The benefits of the research are divided into two, namely practical benefits: providing insight into the construction of phrases in literature, and theoretical benefits: for the author, the results of this research can be utilized as answers to the problems formulated. The method used in this research is descriptive qualitative method. The data in this research are quotes containing nominal, verbal, and adjectival phrases contained in the novel Santri Pilihan Bunda by Salsyabila Falensia. The data collection technique of this research is literature study technique. The data analysis technique uses a structural approach. The results of this study are found 760 phrases in the novel Santri Pilihan Bunda Karya Salsyabila Falensia consisting of 418 nominal phrase data, 264 verbal phrase data, and 78 adjectival phrase data. Based on the results of the phrase findings, there is data on the construction of coordinative nominal phrases: 14 data and subordinate nominal phrases structured: N+N 153 data, N+V 52 data, N+A 29 data, Adv+N 38 data, N+Adv 4 data, Num+N 47 data, N+Num 9 data, and N+Dem 72 data. Coordinative verbal phrases: 6 data and subordinative verbal phrases with the structure: Adv+V 94 data, V+Adv 17 data, V+N 108 data, and V+A 39 data. Coordinative adjectival phrases: 2 data and subordinative adjectival phrases: structured A+N 2 data, A+A 18 data, A+V not found, Adv+A 53 data, and A+Adv 3 data.